PENGGUNAAN MEDIA PUZZLE UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS 4 DI SDIT AL USWAH PAMEKASAN - Agus Saifuddin Amin; Murnie Prirahayu A (LP2M IAI Al Khairat Pamekasan, 2021)
This study aims to increase the activeness of science learning of fourth grade students at SDIT Al Uswah using puzzle media. The use of puzzle media in Natural Science subjects as a solution to increase the learning activity of fourth grade students at SDIT Al Uswah Pamekasan. In the implementation of the improvement plan in cycle 1, it failed, namely when students answered questions from the teacher without learning media, some students experienced difficulties. From 18 students in class 4B SDIT Al Uswah Pamekasan obtained data that 5 students or equivalent to 27.78% can complete their assignments well while 13 students or equivalent to 72.22% of poor work results, with a KKM of 70. Learning It is said to be successful if the class average reaches at least 85%. There were 5 students or 27.78% of Natural Science learning active in cycle 1, while in cycle 2 there were 16 students or 88.89% who succeeded from 18 students overall. This shows that there is an increase in students who complete the KKM 70. Thus, the use of puzzle media in the animal life cycle material for science subjects is very appropriate for fourth grade students of SDIT Al Uswah Pamekasan.